Harmonization of Customs in the Practice of Friday Prayer Legality in Gorontalo City - Asaad, Misbahuddin; Husain, Muhammad Zakir (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2024)
This research aims to explore whether Friday prayers in Gorontalo City are conducted in harmony with both custom and religion. The essence of this implementation lies in how the sources of arguments are interpreted and their application understood, based on the theories and approaches employed. This research adopts a qualitative methodology with an analytical descriptive approach, phenomenological in nature, utilizing data from document studies, observations, and field interviews. The findings reveal that the roles, responsibilities, and tasks assigned to religious leaders and customary institution leaders in carrying out religious and customary processions consistently align with the legitimacy of both religion and custom. The primary goal of customary ceremonial activities is to fulfill religious purposes. The major events of the Friday festivities include sermons and prayers, organized in a specific manner: government officials are seated in the first row to the right of the pulpit, traditional authorities—comprising Bate (the traditional leader) and Wu'u (his deputy)—occupy the second row, while imams and syarak or syara dha'a employees are placed in the first row to the left. Customary institutions are further represented through parades led by government officials, religious authorities, and customary leaders. Ultimately, the purpose of Friday prayers and shaf (row) formations is to foster a solemn atmosphere of unity, enshrouded in ceremonial rhythms of worship. This atmosphere is considered conducive to receiving blessings and attaining merciful salvation. The